Methods for estimating the velocities of the Brazil Current in the pre-salt reservoir area off southeast Brazil (23º S-26º S) - Bilo, Tiago Carrilho (2014)
The Brazil Current (BC) is likely the least observed and investigated subtropical western boundary current in the world. This study proposes a simple and systematic methodology to estimate quasi-synoptic cross-sectional speeds of the BC within the Santos Basin (23∘ S–26∘ S) based on the dynamic method using several combinations of data: Conductivity, temperature, and depth (CTD), temperature profiles, CTD and vessel-mounted Acoustic Doppler Current Profiler (VMADCP), and temperature profiles and VMADCP. All of the geostrophic estimates agree well with lowered Acoustic Doppler Current Profiler (LADCP) velocity observations and yield volume transports of -5.56 ±1.31 and 2.50 ±1.01 Sv for the BC and the Intermediate Western Boundary Current (IWBC), respectively. The LADCP data revealed that the BC flows southwestward and is ∼100 km wide, 500 m deep, and has a volume transport of approximately -5.75 ±1.53 Sv and a maximum speed of 0.59 m s−1. Underneath the BC, the IWBC flows northeastward and has a vertical extent of approximately 1,300 m, a width of ∼60 km, a maximum velocity of ∼0.22 m s−1, and a volume transport of 4.11 ± 2.01 Sv. Our analysis indicates that in the absence of the observed velocities, the isopycnal (σ 0) of 26.82 kg m−3 (∼500 dbar) is an adequate level of no motion for use in geostrophic calculations. Additionally, a simple linear relationship between the temperature and the specific volume anomaly can be used for a reliable first estimate of the BC-IWBC system in temperature-only transects.